Pengaruh Kualitas Produk Dan Kesesuaian Harga Terhadap Peningkatan Penjualan Beras Premium Pada Perum Bulog Divisi Regional Sulawesi Utara Dan Gorontalo (Studi Kasus Pada Konsumen Wilayah Kota Manado) - Intan Puspitasari; Harry J. Sumampouw; Anneke Y. Punuindoong (Universitas Sam Ratulangi, 2018)
The purpose of this research is to determine and obtain a review on the effects of product quality and price compatibility on increasing the sales premium rice at Perum BULOG Division North Sulawesi and Gorontalo (In The Region of Manado City). This is a descriptive quantitative with a sample of 66 respondents that is obtained using accidental sampling method. To test the quality of the instruments, validity and reliability tests are employed, while the data is analyzed using multiple linear regressions method with t test, F test, and coefficient of determination . Therefore, Ho is rejected and Ha is accepted, which means that the independent variables (product quality and price compatibility) simultaneously affect the dependent variables (increasing the sales) positively and significantly. The result of coefficient of determination () shows that the rate of adjusted R Square is 0,713 or 71,3%, which means that the variations of sales increase can be explained by product quality and price compatibility, while the rest 28,7% can be explained by other variables outside the research variables.Â